Detection of TT virus (TTV) by three frequently-used PCR methods targeting different regions of viral genome in children with cryptogenic hepatitis, chronic B hepatitis and hbs carriers - Ergünay, Koray; Gürakan, Figen; Usta, Yusuf; Yüce, Aysel; Karabulut, Hasan Özen Erdem; Ustaçelebi, Şemsettin (The Turkish Journal of Pediatrics, 2008)
This study was designed so that three sensitive and widely-used polymerase chain reaction (PCR) methods for the detection of TT virus or Torque Teno virus (TTV) would be simultaneously applied to a large number of subjects to evaluate performances of the various PCR protocols with different genotype sensitivities. Sera were collected from 92 children admitted to Hacettepe University Ihsan Doğramaci Children’s Hospital Pediatric Gastroenterology Unit (17 cryptogenic chronic hepatitis, 17 asymptomatic HBs carriers, 18 chronic HBV patients and 40 healthy children). TTV DNA was detected via nested N22, nested 3’-UTR and 5’-UTR PCRs for all samples. Differences in TTV D N A detection prevalences were n o t statistically significantbetween the study groups with all TTV DNA and liver enzyme levels. A significant agreement between PCR methods that target UTR was observed. TTV detection rate increased with age, suggesting a non-parenteral, environmental exposure to the virus for the study population.